Artificial 64-Residue HIV-1 Enhancer-Binding Peptide Is a Potent Inhibitor of Viral Replication in HIV-1-Infected Cells - Mouhssin Oufir; Leslie R. Bisset; Stefan R. K. Hoffmann; Gongda Xue; Stephan Klauser; Bianca Bergamaschi; Alain Gervaix; Jürg Böni; Jörg Schüpbach; Bernd Gutte (Advances in Virology)
An artificial HIV-1 enhancer-binding peptide was extended by nine consecutive arginine residues at the C-terminus and by the nuclear localization signal of SV40 large T antigen at the N-terminus. The resulting synthetic 64-residue peptide was found to bind to the two enhancers of the HIV-1 long terminal repeat, cross the plasma membrane and the nuclear envelope of human cells, and suppress the HIV-1 enhancer-controlled expression of a green fluorescent protein reporter gene. Moreover, HIV-1 replication is inhibited by this peptide in HIV-1-infected CEM-GFP cells as revealed by HIV-1 p24 ELISA and real-time RT-PCR of HIV-1 RNA. Rapid uptake of this intracellular stable and inhibitory peptide into the cells implies that this peptide may have the potential to attenuate HIV-1 replication in vivo.